Electronic Nursing Care Reminders. (May 2015) - Piscotty, Ronald J.; Kalisch, Beatrice; Gracey-Thomas, Angel; Yarandi, Hossein
<x xml:space="preserve">Abstract</x> OBJECTIVE: The aim of this study is to report the results of a replication study of the relationship between self-reported nursing care reminder (NCR) use and missed nursing care. DESIGN: A descriptive cross-sectional correlational design was used. The sample (N = 124) was composed of medical/surgical and ICU RNs working on acute care hospital units in a large Midwestern teaching hospital. METHODS: The MISSCARE Survey, Nursing Care Reminders Usage Survey, and the Impact of Health Care Information Technology Survey were used to collect data. Adjusted hierarchical multiple regression was used to determine study outcomes. RESULTS: Nurses who use NCRs more frequently have decreased reports of missed nursing care. Nurses who perceive the impact of healthcare technology as positive on their practice also have decreased missed nursing care. CONCLUSION: The results of this study suggest that NCRs are an effective intervention to decrease missed nursing care in acute care hospitals.